The Relationship Between Plasma Osteoprotegerin and Endothelium-Dependent Arterial Dilation in Type 2 Diabetes - Xiang, Guang-da; Xu, Lin; Zhao, Lin-shuang; Yue, Ling; Hou, Jie (Diabetes (New York, N.Y.), 2006)
The Relationship Between Plasma Osteoprotegerin and Endothelium-Dependent Arterial Dilation in Type 2 Diabetes Guang-da Xiang , Lin Xu , Lin-shuang Zhao , Ling Yue and Jie Hou Department of Endocrinology, Wuhan General Hospital of Guangzhou Command, Wuhan, Hubei Province, China Address correspondence and reprint requests to Dr. Xiang Guang-da, Department of Endocrinology, Wuhan General Hospital of Guangzhou Command, Wuluo Road 627, Wuhan 430070, Hubei Province, P.R. China. E-mail: guangda64athotmail.com Abstract Osteoprotegerin is a recently identified inhibitor of bone resorption. Recent studies indicate that osteoprotegerin also acts as an important regulatory molecule in the vasculature. The purpose of this study was to investigate the relationship between plasma osteoprotegerin levels and endothelium-dependent arterial dilation in type 2 diabetic patients. The study subjects included 40 newly diagnosed type 2 diabetic patients and 46 healthy subjects. All patients were given insulin therapy for 6 months. Plasma osteoprotegerin concentration was measured in duplicate by a sandwich enzyme-linked immunosorbent assay method, and high-resolution ultrasound was used to measure brachial artery diameter at rest, after reactive hyperemia, and after sublingual glyceryltrinitrate. The plasma osteoprotegerin level in patients before treatment was 3.36 ± 0.32 ng/l, which was significantly higher than that in control subjects (2.38 ± 0.25 ng/l, P < 0.001). After 6 months of treatment, osteoprotegerin levels decreased markedly (2.83 ± 0.34 ng/l, P < 0.001). Flow-mediated endothelium-dependent arterial dilation in patients before treatment was 3.21 ± 0.52%, which was significantly lower than that in control subjects (4.46 ± 0.56%, P < 0.01), and it improved markedly after 6 months of treatment (4.03 ± 0.49%, P < 0.01). In multivariate analysis, osteoprotegerin was significantly associated with endothelium-dependent arterial dilation, fasting blood glucose (FBG), HbA 1c (A1C), and ultrasensitive C-reactive protein (CRP) at baseline ( P < 0.01). The absolute changes in osteoprotegerin showed significant correlation with changes in endothelium-dependent arterial dilation, FBG, A1C, and CRP in diabetic patients during the course of treatment ( P < 0.01). This study shows that plasma osteoprotegerin levels are elevated in newly diagnosed diabetic patients and are significantly associated with endothelial function. Footnotes apo, apolipoprotein; CRP, C-reactive protein; FBG, fasting blood glucose; Lp(a), lipoprotein(a); RANKL, receptor activator of nuclear factor-κB ligand; UAER, urinary albumin excretion rate. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact Accepted March 27, 2006. Received February 19, 2006. DIABETES